The area is given by:
A = Ab + Al
Where,
Ab: base area
Al: lateral area
The area of the base is:
Ab = (3/2) * (L ^ 2) * (root (3))
Where,
L: side of the hexagon.
Substituting we have:
Ab = (3/2) * (4 ^ 2) * (root (3))
Ab = (3/2) * (16) * (root (3))
Ab = 24raiz (3)
The lateral area is:
Al = (6) * (1/2) * (b) * (h)
Where,
b: base of the triangle
h: height of the triangle
Substituting we have:
Al = (6) * (1/2) * (4) * (6)
Al = 72
The total area is:
A = 24raiz (3) + 72
Answer:
A = 24raiz (3) + 72
Answer:
My name is Jeremiah
Step-by-step explanation:
We need to solve the zeroes of the given expression x² - 13x + 30 = 0 and we need to apply zero product property.First, we need to identify the two numbers which will result to -13 when added and it will result to 30 when multiplied. These two numbers are -3 and -10. Then, we can proceed with the solution such as:
x² - 13x + 30 = 0
(x-3) (x- 10) =0
From above, we have already the two zero product:
x-3 = 0
x1 = 3
x-10 =0
x2 =10
The answers are x1 = 3 and x2 = 10.
<span>6[5(3-9)-1]+2
order of operations:
Parentheses
Exponents
Multiplication and Division together
Addition and Subtraction together
</span><span>6[5(3-9)-1]+2
6[5(-6)-1]+2
6[-30-1]+2
6[-31]+2
-186+2
-184
7(8-2)+4
7(6)+4
42+4
46
-184/46
-82/23
about -3.6
</span>